Ureteroscopy for management of ureteric calculi: Five years experience in Erbil, Iraq - Al Bazzaz, Wishyar Jamal; Toma, Tarq Aziz (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Retrograde ureteroscope has recently gained a broaden indication for use in from diagnostic to a variety of disorders that occur in the upper urinary tract. This study aimed to review our five years experience with ureteroscopic management for ureteral stones and to compare our rates of efficacy and safety of ureteroscopy with other centers. Methods: Review of 736 consecutive patients who underwent ureteroscopic procedures for the treatment of upper urinary tract problems between January 2010 and January 2015 was done in Erbil, Iraq. Out of those patients, 587 patients underwent a ureteroscopic procedure for the treatment of ureteric calculi. The studied variables were patients and stones characteristics, in addition to the mean operative time and mean hospital stay, the stone-free rate, and complication rates were also calculated. Results: The overall success rate (complete stone clearance) in 587 patients was 550 patients (93.7%). Mean operative time was 26.1 minutes and mean hospital stay was <24 hours. The overall complication rate was 12%. The intra-operative complication rate was 3.2%, the early postoperative complication rate was 8 %, and the late postoperative complication rate was 0.85%. Conclusion: Growing skill and experience of ureteroscopy will lead to a significant increase in the success rate and reduce complications.